Crise e saúde mental na adolescência: a história sob a ótica de quem vive - Rossi, Lívia Martins (2018)
Several studies indicate that adolescents are more vulnerable to the development of mental health problems. However, there is also a lack of researches that focuses on the experience of psychic suffering and attention to the adolescent mental health, including the experience of the mental health crisis. The present study aimed to identify a perception and trajectory of adolescents who experienced a mental health crisis and their responsible family members. The Oral History method was used to collect the narratives of five adolescents between the ages of 16 and 17, users of a Psychosocial Care Center (CAPSij) located in a medium-sized city in the interior of the State of São Paulo. Open-ended statements were applied and the responsible family members were also questionated. The interviews were audio-recorded, fully transcribed, textualized and the material was analyzed through the thematic and content method. Based on the results, it was observed that the participants approach the experience of the crisis in an individualized way, linking it especially to depressive symptoms, ideation and suicide attempt. The reports of suffering refer to the relationships between peers and the family context, whose adversities are considered as possible triggers of crisis processes. Regarding the treatment, was recognized resistance to adhesion, use of medication and the activities offered by the care service, and CAPSij is seen as a reference, sometimes as an absence of supporting. It is also perceived the experience of the crisis as a possibility of transformation of the relationships between adolescents and their families, and the trajectory of access to the service, which goes through the emergency room and the CAPS III before the assistance at CAPSij. The present study, when focusing on the history of adolescents about their experience of the crisis, signals the power that can emerge from processes which the listening and participation of adolescents is guaranteed in the context of care. Therefore it subsidizes important reflections for the professionals who deal with this population in strategic services of mental health care and beyond in order to effect the active participation in the care process, valued in the Brazilian mental health policy, and to favor dynamics of engagement and social participation, based on actions to promote mental health.